QRIS, P2P LENDING, AND MSME SUSTAINABILITY: THE MEDIATING ROLE OF CAPITAL STRUCTURE - Sindy; Winnie; Erica Mentari Br Purba; Rafida Khairani; Nasib (ZILLZELL MEDIA PRIMA, 2026)
This study examines the impact of QRIS and peer-to-peer (P2P) lending on the sustainability of micro, small, and medium enterprises (MSMEs), with capital structure as a mediating variable in Medan Petisah. The rapid development of digital financial services has provided new opportunities for MSMEs to improve financial access and operational efficiency. This research employs a quantitative approach using survey data collected from MSME actors. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that QRIS and P2P lending have a significant positive effect on capital structure and MSME sustainability. Furthermore, capital structure partially mediates the relationship between financial technology usage and business sustainability. These findings indicate that digital financial adoption not only enhances access to funding but also improves the financial structure of MSMEs, contributing to long-term sustainability. This study provides empirical evidence on the role of financial technology in strengthening MSME performance in urban areas.